Analisis Yuridis Pembuktian Sengketa Transfer Pricing - Arrisman, Arrisman; Fauzi, Ahmad (Syntax Corporation, 2025)
This research is about the juridical analysis of the proof of transfer pricing disputes with an example of the case of the Tax Court decision No.Put.74576/PP/M.IB/15/2016. The ruling granted an appeal filed by PT HI, a foreign investment company from Japan. Transfer Pricing or TP occurs in transactions involving